Application of organic chelating molecule, n-type doped perovskite battery and preparation method of n-type doped perovskite battery
By using multiple electron-donating groups to coordinate with lead ions in perovskites, the stability and efficiency bottlenecks of perovskite solar cells are solved, and efficient carrier separation and stability improvement of perovskite films are achieved.
Patent Information
- Application Number
- CN202510641704.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-19
- Publication Date
- 2025-08-19
AI Technical Summary
The prior art is difficult to achieve the stability and carrier separation efficiency of perovskite solar cells while maintaining high efficiency. The traditional doping strategy has stability problems and insufficient improvement of carrier concentration, and lacks coordinated optimization of defective state density and energy band structure.
Organic chelating molecules containing multiple electron donating groups are used as dopants and passivators. By coordinating with lead ions in perovskites, electron cloud density is enhanced, low-coordinated Pb2+ ions are passivated, deep electron trap effect is eliminated, and downward band bending is formed at the perovskite/electron transport layer interface to promote electron extraction.
It significantly improves the open circuit voltage and photoelectric conversion efficiency, enhances the stability of the perovskite film, inhibits non-radiative recombination and ion migration, and improves the filling factor and photooxygen stability.
Smart Images

Figure CN120513013A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of semiconductor devices, and in particular relates to an application of an organic chelate molecule, an n-type doped perovskite battery and a preparation method thereof. Background Art
[0002] Perovskite materials have become a research hotspot in the photovoltaic field due to their excellent optoelectronic properties, tunable optical band gap (1.4-2.3eV), and solution processability. The certified record of photovoltaic conversion efficiency (PCE) of single-junction organic-inorganic hybrid perovskite solar cells (PSCs) has exceeded 27.0%, showing great commercial potential. However, the intrinsic carrier concentration of perovskite materials is low (for example, the carrier concentration of CH3NH3PbI3 is usually less than 10 15 cm -3 ), which makes it difficult to form an effective space charge region and a local built-in electric field, severely restricting the separation efficiency of photogenerated carriers and the ability to suppress interface non-radiative recombination.
[0003] Currently, n-type doping is one of the core methods for regulating the electrical properties of perovskites. The carrier concentration can be increased by introducing iodine vacancies (Ivac), but this method has significant drawbacks: 1. Stability issues: Iodine vacancies are prone to migration under the action of an electric field, resulting in a photocurrent hysteresis effect; under the synergistic effect of oxygen and light, Ivac catalyzes the generation of superoxide ions (O2 - ), accelerating the decomposition of perovskite; 2. Performance limitations: Ivac is a shallow energy level defect. Although it can increase the electron concentration, it cannot effectively adjust the Fermi level position, and high concentration of vacancies will introduce non-radiative recombination centers.
[0004] Although traditional chemical doping strategies (such as A-site / B-site high-valence ion doping) can improve stability, they are limited by ion size mismatch (such as Rb + , K + The lattice stress) and crystal structure phase transition risk make it difficult to achieve controllable n-type doping while maintaining high efficiency. For example, the introduction of Cs into CsPbI3 + A concentration exceeding 3% will induce phase separation, resulting in a sharp drop in device efficiency.
[0005] Molecular doping technology (such as 4PACz, DCBP, etc.) has achieved some performance improvements through surface coordination or energy level regulation. For example, DCBP molecules chelate Ag through pyridine groups. + The electron-withdrawing property of 4PACz can move the Fermi level of perovskite from the high energy side of the band gap to the low energy side, achieving pn-type transition. However, this method still faces the problems of poor molecular doping uniformity and low doping efficiency (the electron concentration is less than 1016 cm -3 ) and lack of coordinated optimization of defect state density and band structure.
[0006] Therefore, developing an n-type doping strategy that can not only precisely control the local electron concentration and Fermi level position of perovskite but also suppress defect migration and decomposition has become the key to breaking through the bottleneck of perovskite solar cell efficiency and stability. Summary of the Invention
[0007] One of the purposes of the present invention is to provide an application of an organic chelate molecule, which coordinates with lead ions through the chelate effect, thereby increasing the electron cloud density around the lead ions and reducing the low-coordinated Pb on the perovskite surface. 2+ The Coulomb attraction of ions to transport electrons eliminates Pb 2+ ions, and thus promote the deep electron trap effect of Pb 2+ The positive charge effect of the ions achieves n-type doping.
[0008] A second object of the present invention is to provide an n-type doped perovskite cell using the perovskite dopant;
[0009] A third object of the present invention is to provide a method for preparing the n-type doped perovskite cell.
[0010] In order to achieve the above object, the present invention provides the following technical solutions:
[0011] The present invention provides an application of an organic chelate molecule, specifically an application in terms of a dopant and a passivator for a perovskite active layer.
[0012] The organic chelating molecule contains several electron-donating groups;
[0013] The electron-donating groups include amine (-NH2), hydroxyl (-OH), thiol (-SH) and carboxyl (-COOH);
[0014] The organic chelating molecules include tris(2-aminoethyl)amine (TAEA), ethylenediaminetetraacetic acid (EDTA), and ethylenediaminetetraethanol (THEED).
[0015] Preferably, the organic chelating molecule is tris(2-aminoethyl)amine (TAEA).
[0016] The structural formula of the tris(2-aminoethyl)amine is as follows:
[0017]
[0018] The structural formula of the EDTA is as follows:
[0019]
[0020] The structural formula of the ethylenediaminetetraethanol is as follows:
[0021]
[0022] The present invention also provides an n-type doped perovskite cell using the organic chelating molecule as a dopant and a passivator, wherein the n-type doped perovskite cell comprises a transparent conductive substrate, a hole transport layer, a light absorption layer, a modification layer, an electron transport layer, a cathode modification layer and a top electrode stacked in sequence from bottom to top.
[0023] The materials used for the conductive substrate include transparent conductive materials such as indium tin oxide (ITO), fluorine doped tin oxide (FTO), aluminum zinc oxide (AZO) and metal nanowire film;
[0024] The hole transport layer includes nickel oxide (NiO x ), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), poly(3,4-ethylenedioxythiophene) (PEDOT), [2-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphoric acid (Meo-2PACz), cuprous iodide (CuI), copper thiocyanate (CuSCN);
[0025] The light absorbing layer is a perovskite with an ABX3 structure, wherein the A position includes cations (methylamine ions, formamidine ions and cesium ions) or a blend of different cations, and the B position includes divalent metal ions (Pb 2+ 、Sn 2+ ) or a blend of different divalent metal ions, X is a halogen ion (Cl - Br - , I - ) or a blend of different halide ions;
[0026] The modified layer is a film composed of organic chelating molecules containing multiple electron-donating groups;
[0027] The organic chelating molecules are prepared into films by a solution coating method or a vapor deposition method.
[0028] The solution coating method includes any one of spin coating, blade coating, spray coating, slit coating and Czochralski method.
[0029] The electron transport layer includes fullerene and its derivatives, non-fullerene electron acceptors, titanium dioxide (TiO2), tin dioxide (SnO2), and zinc oxide (ZnO);
[0030] The cathode modification layer comprises bathocuproine (BCP), bathophenanthroline (Bphen) and lithium fluoride (LiF).
[0031] The top electrode includes a metal (silver, gold, aluminum, copper, etc.) electrode or a carbon electrode.
[0032] Preferably, the conductive substrate comprises a glass substrate and an ITO transparent conductive layer deposited on the glass substrate;
[0033] The hole transport layer is made of PTAA.
[0034] The light absorbing layer is an organic-inorganic hybrid perovskite Cs deposited by a two-step method. 0.05 FA 0.83 MA 0.12 PbI 2.87 Br 0.13 ;
[0035] The modified layer is made of tris(2-aminoethyl)amine (TAEA) dissolved in isopropyl alcohol;
[0036] The electron transport layer is made of [6,6]-Phenyl-C61-butyric acid methylester (PC 61 BM), the thickness of the electron transport layer is 10 to 30 nm.
[0037] The cathode modification layer is BCP, and the thickness of the cathode modification layer is 5-9 nm.
[0038] The top electrode is made of copper (Cu), and the thickness of the top electrode is 60-100 nm.
[0039] The present invention also provides a method for preparing the n-type doped perovskite battery, comprising the following steps:
[0040] S1. Pretreatment of the conductive substrate: Using ITO conductive glass as the substrate, ultrasonically clean it with deionized water, acetone, and isopropyl alcohol for 10-20 minutes. Drain the solvent with nitrogen and dry it in an oven. Then, treat it with UV-ozone for 10-20 minutes. The entire hole transport layer preparation process was performed in a nitrogen glove box.
[0041] S2. Preparation of a hole transport layer: Dissolve 2-10 mg of PTAA powder in 1 mL of chlorobenzene to prepare a PTAA solution; drop the PTAA solution onto an ultrasonically cleaned ITO conductive substrate and spin-coat the substrate at 3000-5000 rpm for 20-40 seconds. Finally, anneal the substrate on a hot plate at 80-120°C for 10-30 minutes to evaporate the solvent, thereby obtaining a PTAA film.
[0042] S3. Preparation of light absorption layer: Weigh 553mg of lead iodide and 15mg of cesium iodide and put them into 1mL of DMF solvent at the same time, place them on a 65℃ hot stage for 8h to fully dissolve them, and obtain a lead salt precursor solution; weigh 60mg of iodomethane, 6mg of chloromethylamine and 6mg of bromomethylamine and put them into 1mL of isopropanol solvent at the same time, place them on a 65℃ hot stage for 0.5h to fully dissolve them, and obtain an amine salt precursor solution; drop the lead salt precursor solution on the hole transport layer, spin-coat it at a speed of 3000-5000rpm for 20-40s, then drop the amine salt precursor solution on it, and spin-coat it at a speed of 3000-5000rpm for 20-40s. Finally, place it on a hot stage at 80-120℃ for 5-10min to evaporate the solvent and promote perovskite crystallization to obtain a perovskite film with a thickness of about 600nm; the entire preparation process of the light absorption layer is carried out in a nitrogen glove box;
[0043] S4. Prepare the modified layer: Add TAEA liquid dropwise to isopropyl alcohol (IPA) to create a 0.2-0.8 mM TAEA solution. Apply the TAEA solution to the light-absorbing layer and spin-coat at 5000-7000 rpm for 20-40 seconds. Finally, anneal on a hot plate at 80-120°C for 5-10 minutes to evaporate the solvent.
[0044] TAEA coordinates with lead ions in the perovskite to achieve n-type doping and passivates defects on the perovskite surface and grain boundaries. The entire process of preparing the modified layer is carried out in a nitrogen glove box.
[0045] S5. Prepare electron transport layer: weigh 12-18 mg PC 61 BM powder was put into 1 mL of chlorobenzene (CB) solvent to prepare PC 61 BM solution, and then placed on a 65℃ hot plate to heat for 4 hours to fully dissolve it. 61 The BM solution was dropped onto the surface of the light absorbing layer / modified layer, and the film was formed by spin coating at a speed of 2000-4000 rpm for 10-40 seconds. Finally, the film was placed on a hot plate at 75-85°C for annealing for 8-12 minutes to evaporate the solvent to obtain PC. 61 BM electron transport layer; the entire preparation process of the electron transport layer was carried out in a nitrogen glove box;
[0046] S6. Preparation of cathode modification layer: Place the sample prepared above into a vacuum chamber and pump the pressure to <5×10 -4 Pa, 5-10 nm thick BCP is evaporated on the electron transport layer by thermal evaporation method, and the evaporation rate is The entire preparation process of the cathode modification layer was carried out in a nitrogen glove box;
[0047] S7. Prepare the top electrode: Place the sample prepared above into a vacuum chamber and pump the pressure down to <5×10-4 Pa, 60-100 nm thick Cu is evaporated on the cathode modification layer by thermal evaporation method, and the evaporation rate is The entire preparation process of the top electrode was carried out in a nitrogen glove box.
[0048] Beneficial effects of the present invention:
[0049] (1) The present invention is the first to use an organic chelate molecule containing multiple electron-donating groups to passivate perovskite defects. The invented passivation technology is simple and easy to repeat, uses a solution processing technology suitable for large-scale preparation, and is carried out under mild conditions at low temperature and without catalyst, which is conducive to industrial production. Due to the volatility of iodine, I vacancy defects are most likely to form on the perovskite surface and grain boundaries during the preparation process, and a large amount of uncoordinated Pb 2+ , becoming the main non-radiative recombination center. Organic chelating molecules with multiple electron-donating groups can provide lone pair electrons, which react with uncoordinated Pb in the perovskite through Lewis acid-base reaction. 2+ The combination of the two passivates the I vacancy defect. Therefore, through the passivation strategy, the open circuit voltage of the perovskite solar cell is significantly increased from 1.08V to 1.16V, the photoelectric conversion efficiency is increased from 19.4% to 23.4%, and non-radiative recombination is suppressed;
[0050] (2) The chelating effect of the organic chelating molecules provided by the present invention, which are composed of multiple electron-donating groups, weakens the low-coordinated Pb on the perovskite surface. 2+ The Coulomb attraction of ions to transport electrons eliminates Pb 2+ ions, and thus promote the deep electron trap effect of Pb 2+ The positive charge effect of the ions enables n-type doping. N-type doping of perovskites can form a downward band bend at the perovskite / ETL interface, promoting electron extraction. As a result, the fill factor of doped perovskite solar cells increases from 76.2% to 82.9%.
[0051] (3) The n-doping strategy of the n-type doped perovskite cell provided by the present invention does not rely on the formation of iodine vacancies, and the stability of the perovskite film is also enhanced. 0.1 FA 0.9 The absorption intensity of PbI3 perovskite film at 700nm decreased by 10% after 44h of photooxidation aging. 0.1 FA 0.9 The absorption intensity of the PbI3 perovskite film at 700nm still maintains 92% after 400h of photooxidation aging, which is more than 10 times the photooxidation stability. 2+ The combination of iodine vacancies and oxygen molecules prevents the adsorption of oxygen molecules and the formation of superoxide ions.
[0052] (4) The migration of ions in the n-type doped perovskite battery provided by the present invention requires the assistance of defects, so the perovskite defect state density will affect ion migration. After TAEA passivation of the perovskite, the perovskite defect state density is reduced, ion migration is therefore suppressed, and the ion migration activation energy is increased from 0.43eV to 0.67eV. The migration of ions in perovskite under bias, light or high temperature conditions will lead to the loss and decomposition of perovskite components, which is an important reason for the poor stability of perovskite. TAEA's inhibition of ion migration can effectively improve the intrinsic stability of perovskite. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 Schematic diagram of the structure of the perovskite solar cell prepared in Example 1; wherein the reference numerals are: 1, transparent conductive substrate; 2, hole transport layer; 3, light absorption layer; 4, modification layer; 5, electron transport layer; 6, cathode modification layer; 7, top electrode;
[0054] Figure 2 1 is a comparison diagram of the reverse-scan JV curves of the perovskite solar cells prepared in Example 1 and Comparative Example 1;
[0055] Figure 3 Graph showing changes in fill factor of the perovskite solar cells prepared in Example 1 and Comparative Example 1 under different light intensities;
[0056] Figure 4 a is the absorption spectrum of the perovskite film during photooxidative aging after iodine vacancies were introduced by IPA rinsing; Figure 4 b is the absorption spectrum of the perovskite film prepared in Example 1 during the photooxidation aging process; Figure 4 c is the absorption intensity of the absorption spectrum at 700 nm;
[0057] Figure 5 Ultraviolet photoelectron spectra (UPS) of the perovskite films prepared in Example 1 and Comparative Example 1;
[0058] Figure 6 2 is a defect state density diagram of the perovskite films prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0059] The following examples are further listed in conjunction with the accompanying drawings and specific embodiments to describe the present invention in detail. It should also be understood that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention all fall within the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description of the text, and are not limited to the specific numerical values exemplified below.
[0060] Example 1
[0061] (1) Pretreatment of the transparent conductive substrate: ITO glass with a transmittance of >85%, a square resistance of 15Ω / □, and a size of 15mm*15mm was used as the device substrate. The substrate was ultrasonically cleaned in deionized water, acetone, and isopropyl alcohol for 15 minutes. The solvent was blown away with nitrogen and then placed in an 85°C oven. Finally, it was placed in a UV ozone machine for 15 minutes to remove residual organic impurities and enhance the wettability of the solution on the substrate.
[0062] (2) Preparation of hole transport layer: 2 mg of PTAA powder was dissolved in chlorobenzene and then placed on a 65°C hot plate to completely dissolve. The prepared PTAA solution was dropped onto the conductive substrate treated in step (1) using a pipette and spin-coated at 6000 rpm for 30 seconds to form a film. The film was then placed on a 100°C hot plate for 10 minutes to evaporate the solvent, thereby obtaining the PTAA hole transport layer. The entire preparation of the hole transport layer was carried out in a nitrogen glove box.
[0063] (3) Preparation of light absorption layer: Weigh 553 mg of lead iodide and 15 mg of cesium iodide and place them in 1 mL of DMF solvent at the same time, place them on a 65°C hot plate for 8 hours to fully dissolve them, and obtain a lead salt precursor solution. Weigh 60 mg of iodomethane, 6 mg of chloromethylamine, and 6 mg of bromomethylamine and place them in 1 mL of isopropanol solvent at the same time, place them on a 65°C hot plate for 0.5 hours to fully dissolve them, and obtain an amine salt precursor solution. Drop the lead salt precursor solution on the PTAA film and spin-coat it at a speed of 3000-5000 rpm for 20-40 seconds. Then drop the amine salt precursor solution on the film and spin-coat it at a speed of 3000-5000 rpm for 20-40 seconds. Finally, place it on a 80-120°C hot plate for 5-10 minutes to evaporate the solvent and promote perovskite crystallization, obtaining a perovskite film with a thickness of approximately 600 nm. The entire preparation process of the light absorption layer was carried out in a nitrogen glove box.
[0064] (4) Preparation of the Modification Layer: TAEA liquid was added dropwise to IPA solvent to prepare a 0.2 mM TAEA solution. The TAEA solution was dropped onto the perovskite film and spin-coated at 5000 rpm for 30 seconds. Finally, the film was annealed on a hot plate at 150°C for 3 minutes to evaporate the solvent. The entire preparation of the modification layer was performed in a nitrogen glove box.
[0065] (5) Preparation of electron transport layer: weigh 15 mg PC 61 BM powder was put into 1 mL of chlorobenzene solvent to prepare PC 61 BM solution, and then placed on a 65℃ hot plate to heat for 4 hours to fully dissolve it. 61 The BM solution was dropped onto the perovskite / TAEA surface and spin-coated at 3000 rpm for 30 seconds to form a film. Finally, the film was annealed on a hot plate at 80°C for 10 minutes to evaporate the solvent and obtain PC. 61 BM electron transport layer. The entire preparation process of the electron transport layer was carried out in a nitrogen glove box.
[0066] (6) Preparation of cathode modification layer: Place the sample prepared above into a vacuum chamber and pump the air pressure to <10 -4 Pa, BCP was evaporated on PC by thermal evaporation method. 61 On the BM layer, the evaporation rate is The thickness is 7 nm. The cathode modification layer was prepared in a nitrogen glove box.
[0067] (7) Preparation of top electrode: Place the sample prepared above into a vacuum chamber and pump the pressure to <10 -4 Pa, Cu was evaporated on the BCP layer by thermal evaporation method, and the evaporation rate was The thickness is ∼80 nm. The top electrode preparation was performed entirely in a nitrogen glove box.
[0068] The structure of the perovskite solar cell prepared in Example 1 is as follows Figure 1 As shown, from bottom to top, they are a transparent conductive substrate, a hole transport layer, a light absorption layer, a modification layer, an electron transport layer, a cathode modification layer and a top electrode.
[0069] Comparative Example 1
[0070] (1) Pretreatment of the conductive substrate: ITO glass with a transmittance of >85%, a square resistance of 15Ω / □, and a size of 15mm*15mm was used as the device substrate. The substrate was sequentially immersed in deionized water, acetone, and isopropyl alcohol for ultrasonic cleaning for 15 minutes. The solvent was blown away with nitrogen and then placed in an 85℃ oven. Finally, it was placed in a UV ozone machine for 15 minutes to remove residual organic impurities and enhance the wettability of the solution on the substrate.
[0071] (2) Preparation of hole transport layer: 2 mg of PTAA powder was dissolved in 1 mL of chlorobenzene and then placed on a 65°C hot plate to completely dissolve. The prepared PTAA solution was dropped onto the conductive substrate treated in step (1) using a pipette and spin-coated at 6000 rpm for 30 seconds to form a film. The film was then placed on a 100°C hot plate for 10 minutes to evaporate the solvent to obtain the PTAA hole transport layer. The entire preparation of the hole transport layer was carried out in a nitrogen glove box.
[0072] (3) Preparation of light absorption layer: Weigh 553 mg of lead iodide and 15.6 mg of cesium iodide and place them in 1 mL of DMF solvent at the same time, place them on a 65°C hot plate for 8 hours to fully dissolve them, and obtain a lead salt precursor solution. Weigh 60 mg of iodomethane, 6 mg of chloromethylamine, and 6 mg of bromomethylamine and place them in 1 mL of isopropanol solvent at the same time, place them on a 65°C hot plate for 0.5 hours to fully dissolve them, and obtain an amine salt precursor solution. Drop the lead salt precursor solution on the PTAA film and spin-coat it at a speed of 3000-5000 rpm for 20-40 seconds. Then drop the amine salt precursor solution on the film and spin-coat it at a speed of 3000-5000 rpm for 20-40 seconds. Finally, place it on a 80-120°C hot plate for 5-10 minutes to evaporate the solvent and promote perovskite crystallization, obtaining a perovskite film with a thickness of approximately 600 nm. The entire preparation of the light absorption layer was carried out in a nitrogen glove box.
[0073] (4) Preparation of electron transport layer: weigh 15 mg PC 61 BM powder was put into 1 mL of chlorobenzene solvent to prepare PC 61 BM solution, and then placed on a 65℃ hot plate to heat for 4 hours to fully dissolve it. 61 The BM solution was dropped onto the perovskite surface and spin-coated at 3000 rpm for 30 seconds to form a film. Finally, it was placed on a hot plate at 80°C for 10 minutes to evaporate the solvent and obtain PC. 61 BM electron transport layer. The entire preparation process of the electron transport layer was carried out in a nitrogen glove box.
[0074] (5) Preparation of cathode modification layer: Place the sample prepared above into a vacuum chamber and pump the air pressure to <10 -4 Pa, BCP was evaporated on PC by thermal evaporation method. 61 On the BM layer, the evaporation rate is The thickness is 7 nm. The cathode modification layer was prepared in a nitrogen glove box.
[0075] (6) Preparation of top electrode: Place the sample prepared above into a vacuum chamber and pump the pressure to <10 -4 Pa, Cu was evaporated on the BCP layer by thermal evaporation method, and the evaporation rate was The thickness is ∼80 nm. The top electrode preparation was performed entirely in a nitrogen glove box.
[0076] Comparative Example 1 does not use TAEA for passivation compared to Example 1. The reverse scan JV curves of the perovskite solar cells prepared in Example 1 and Comparative Example 1 are as follows: Figure 2 In Comparative Example 1, the prepared perovskite solar cell has an open circuit voltage of 1.08 V and a short circuit current of 23.6 mA cm -2 , the fill factor is 76.2%, and the photoelectric conversion efficiency is 19.4%. In Example 1, the open circuit voltage of the prepared perovskite solar cell is significantly increased to 1.16V, and the short circuit current is 24.3mAcm -2 , the fill factor increased to 82.9%, and the photoelectric conversion efficiency increased to 23.4%. The increase in open-circuit voltage proves the passivation effect of TAEA on perovskite, suppressing the non-radiative recombination loss of the device.
[0077] Compared with Comparative Example 1, the significant improvement in the fill factor of the perovskite solar cell prepared in Example 1 is due to the n-doping effect of TAEA to improve the electron extraction efficiency. Figure 3 As shown, when the light intensity is weak (<10mW cm -2 ), the photogenerated electrons in both Comparative Example 1 and Example 1 can be effectively transferred from the perovskite layer to the ETL layer. -2 , the concentration of photogenerated carriers also increases accordingly. The fill factor of the device in Comparative Example 1 decreases significantly because the electrons cannot be completely extracted, while the fill factor of the device in Example 1 is more stable under high light intensity.
[0078] like Figure 4 As shown, the n-doping treatment by introducing iodine vacancies makes Cs 0.1 FA 0.9 The absorption intensity of PbI3 perovskite film at 700nm decreased by 10% after 44h of photooxidation aging. 0.1 FA 0.9 After 400 hours of photooxidation aging, the absorption intensity of the PbI3 perovskite film at 700nm still maintains 92%, achieving a photooxidation stability of more than 10 times. In the presence of oxygen and light, iodine vacancies will assist oxygen in generating highly chemically active superoxide ions, greatly accelerating the decomposition of the film. 2+ The combination of iodine vacancies and oxygen molecules prevents the adsorption of superoxide ions.
[0079] like Figure 5As shown, the Fermi level of the perovskite film prepared in Comparative Example 1 is -4.91eV, which is closer to the bottom of the conduction band (-4.38eV), indicating a weak n-type semiconductor. The Fermi level of the perovskite film prepared in Example 1 shifts 0.29eV toward the bottom of the conduction band relative to that in Comparative Example 1. The n-doping of the perovskite surface by TAEA in Example 1 can increase the degree of band bending at the interface, promoting the extraction of electrons from the perovskite layer to the electron transport layer.
[0080] Figure 6 The defect state density of the perovskite film prepared in Example 1 at different defect depths is lower than that of the perovskite film prepared in Comparative Example 1, demonstrating the passivation effect of TAEA molecules on perovskite.
Claims
1. An application of an organic chelating molecule, characterized in that, The application is specifically the application in the aspects of dopant and passivator of perovskite active layer; the organic chelate molecule contains several electron-donating groups, including tris(2-aminoethyl)amine, ethylenediaminetetraacetic acid, and ethylenediaminetetraethanol.
2. The use according to claim 1, characterized in that The electron-donating groups include amine groups, hydroxyl groups, thiol groups and carboxyl groups.
3. An n-type doped perovskite battery, characterized in that: The n-type doped perovskite cell comprises a transparent conductive substrate, a hole transport layer, a light absorption layer, a modification layer, an electron transport layer, a cathode modification layer and a top electrode stacked in sequence from bottom to top; the modification layer adopts the organic chelating molecule according to any one of claims 1 or 2.
4. The n-type doped perovskite cell according to claim 3, characterized in that: The organic chelating molecules are prepared into films by a solution coating method or a vapor deposition method; the solution coating method includes any one of a spin coating method, a blade coating method, a spray coating method, a slit coating method, and a Czochralski method.
5. The n-type doped perovskite cell according to claim 3, characterized in that: The conductive substrate is made of transparent conductive materials, including indium tin oxide, fluorine tin oxide, aluminum zinc oxide and metal nanowire film; The materials used in the hole transport layer include nickel oxide, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], poly(3,4-ethylenedioxythiophene), [2-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphoric acid, cuprous iodide, and copper thiocyanate; The light absorbing layer is a perovskite having an ABX3 structure, wherein the A position includes a cation or a blend of different cations, the B position includes a divalent metal ion or a blend of different divalent metal ions, and the X position includes a halogen ion or a blend of different halogen ions; The electron transport layer comprises fullerene and its derivatives, non-fullerene electron acceptors, titanium dioxide, tin dioxide, and zinc oxide; The cathode modification layer includes bathocuproin, bathophenanthroline, and lithium fluoride; The top electrode includes a metal electrode or a carbon electrode.
6. The n-type doped perovskite cell according to claim 5, characterized in that: The conductive substrate comprises a glass substrate and an ITO transparent conductive layer deposited on the glass substrate; The hole transport layer is made of PTAA. The light absorbing layer is an organic-inorganic hybrid perovskite Cs deposited by a two-step method. 0.05 FA 0.83 MA 0.12 PbI 2.87 Br 0.13 ; The modified layer is made of tris(2-aminoethyl)amine dissolved in isopropyl alcohol; The electron transport layer is made of PC dissolved in chlorobenzene. 61 BM; The cathode modification layer is BCP; The top electrode is copper.
7. The n-type doped perovskite cell according to claim 3, characterized in that: The thickness of the light absorption layer is 300-700 nm; the thickness of the electron transport layer is 10-30 nm; the thickness of the cathode modification layer is 5-9 nm; and the thickness of the top electrode is 60-100 nm.
8. A method for preparing an n-type doped perovskite battery according to any one of claims 3 to 7, characterized in that: The following steps are involved: S1. Pretreatment of the conductive substrate: The conductive substrate was ultrasonically cleaned with deionized water, acetone, and isopropyl alcohol; then dried with a nitrogen stream, and then treated with UV ozone to obtain a pretreated conductive substrate layer; S2. Preparation of a hole transport layer: The hole transport layer material is dissolved in a solvent, and then spin-coated on the pretreated conductive substrate layer, and then annealed to obtain a hole transport layer; S3. Preparation of a light absorbing layer: According to the preparation method of the light absorbing layer material, a light absorbing material is prepared on the hole transport layer; and then annealing is performed to obtain a light absorbing layer; S4. Preparation of a modified layer: According to a method for preparing a modified layer material, a modified layer material is prepared on the light absorbing layer; and then annealing to obtain a modified layer; S5. Preparing an electron transport layer: dissolving the electron transport layer material in a solvent, spin-coating the modified layer, and annealing to obtain an electron transport layer; S6. Preparing a cathode modification layer: evaporating the cathode modification layer material onto the electron transport layer by evaporation to obtain a cathode modification layer; S7. Prepare the top electrode: evaporate the top electrode material onto the cathode modification layer to obtain the top electrode, thereby obtaining the n-type doped perovskite cell.
9. The preparation method according to claim 8, characterized in that The specific steps include: S1. Pretreatment of the conductive substrate: Using ITO conductive glass as the substrate, ultrasonically clean it with deionized water, acetone, and isopropyl alcohol for 10-20 minutes. After drying the solvent with nitrogen, place it in an oven and dry it with UV-ozone for 10-20 minutes. The entire hole transport layer preparation process was performed in a nitrogen glove box. S2. Preparation of a hole transport layer: Dissolve 2-10 mg of PTAA powder in 1 mL of chlorobenzene to prepare a PTAA solution; drop the PTAA solution onto an ultrasonically cleaned ITO conductive substrate and spin-coat the substrate at 3000-5000 rpm for 20-40 seconds. Finally, anneal the substrate on a hot plate at 80-120°C for 10-30 minutes to evaporate the solvent, thereby obtaining a PTAA film. S3. Preparation of light absorption layer: Weigh 553 mg of lead iodide and 15 mg of cesium iodide and place them in 1 mL of DMF solvent at the same time, place them on a 65°C hot plate for 8 hours to fully dissolve them, and obtain a lead salt precursor solution; weigh 60 mg of iodomethane, 6 mg of chloromethylamine, and 6 mg of bromomethylamine and place them in 1 mL of isopropanol solvent at the same time, place them on a 65°C hot plate for 0.5 hours to fully dissolve them, and obtain an amine salt precursor solution; drop the lead salt precursor solution on the hole transport layer, and spin-coat it at a speed of 3000-5000 rpm for 20-40 seconds, then drop the amine salt precursor solution on it, and spin-coat it at a speed of 3000-5000 rpm for 20-40 seconds; finally, place it on a hot plate at 80-120°C for 5-10 minutes to evaporate the solvent and promote perovskite crystallization, obtaining a perovskite film with a thickness of approximately 600 nm; the entire preparation process of the light absorption layer was carried out in a nitrogen glove box; S4. Preparation of the modification layer: dissolving the organic chelating molecule in isopropanol solvent to prepare a solution; dropping the resulting solution onto the light absorbing layer, spin coating at 5000-7000 rpm for 20-40 seconds, and finally annealing on a hot plate at 80-120°C for 5-10 minutes to evaporate the solvent; S5. Prepare electron transport layer: weigh 12-18 mg PC 61 BM powder was put into 1 mL of chlorobenzene solvent to prepare PC 61 BM solution, and then placed on a 65℃ hot plate to heat for 4 hours to fully dissolve it; 61 The BM solution was dropped onto the surface of the light absorbing layer / modified layer, and the film was formed by spin coating at a speed of 2000-4000 rpm for 10-40 seconds. Finally, the film was placed on a hot plate at 75-85°C for annealing for 8-12 minutes to evaporate the solvent to obtain PC. 61 BM electron transport layer; the entire preparation process of the electron transport layer was carried out in a nitrogen glove box; S6. Preparation of cathode modification layer: Place the sample prepared in step S5 into a vacuum chamber and pump the pressure to <5×10 -4 Pa, 5-10 nm thick BCP is evaporated on the electron transport layer by thermal evaporation method, and the evaporation rate is The entire preparation process of the cathode modification layer was carried out in a nitrogen glove box; S7. Prepare the top electrode: Place the sample prepared in step S6 into the vacuum chamber and pump the pressure to <5×10 -4 Pa, 60-100 nm thick Cu is evaporated on the cathode modification layer by thermal evaporation method, and the evaporation rate is The entire process of preparing the top electrode is carried out in a nitrogen glove box; after completion, the n-type doped perovskite cell is obtained.
10. The preparation method according to claim 9, characterized in that Step S4 specifically comprises: adding TAEA liquid dropwise to isopropanol solvent to prepare a 0.2-0.8 mM TAEA solution; dropping the TAEA solution onto the light absorbing layer, spin coating at 5000-7000 rpm for 20-40 seconds, and finally annealing on a hot plate at 80-120° C. for 5-10 minutes to evaporate the solvent; TAEA coordinates with lead ions in the perovskite to perform n-type doping and passivates defects on the perovskite surface and grain boundaries; the entire preparation process of the modified layer is carried out in a nitrogen glove box.